Ruined shrines in the Jain temple complex - Temples of India Project Team (Jio Institute, 2024)
The main Jain Temple is surrounded by plain raised plinths to its western and eastern side but the superstructures have not survived. On the southern side i.e., the rear of the main temple has a two small ruined shrines that survive on the plinth and wall remains. Based on the remains in the garbhagriha (sanctum sanctorum), these temple remains can be ascribed to Jain worship. The plinth mouldings of the ruined temples are similar to the plinth mouldings of the main Jain temples.